PROFIL RUMAH TANGGA MISKIN ACEH YANG DIKEPALAI OLEH PEREMPUAN - Izza Hazhiyah; Muhammad Nasir (Syiah Kuala University, 2021)
This Study aims to analyze poverty households in Aceh headed by female who are focused on female headed households aged ≥ 60 years. Variables in this study were taken based on social and economics aspects, include education, profession and health. The authors used a descriptive qualitative analysis method., The data used is secondary data. The data consisted of cross section data, obtained from TKP2K Aceh Province. The results showed that the majority of school participation rates in female headed-households only had elementary school education and were aged ≥ 60 years. The profession sector of female headed-households tends to work as a farmer and plantation, the percentage of female headed-households aged ≥ 60 years who works is very low compared to female headed-households at other age levels. The majority of female headed-households who have chronic diseases and disabilities are mostly found in female headed-households aged ≥ 60 years. Chronic diseases that are most often found in female headed-households are rheumaticsm and hypertension, while disabilities that are most often found are physically disabled and blind.